A Comparison of Covert and Videotape Modeling Strategies for Training Complex Mechanical Assembly Tasks. (September 2014) - Linnerooth, Peter J. N.; Houlihan, Daniel; Lenz, Melissa A.; Buchanan, Jeffrey
Experimentation was conducted comparing videotape self-modeling and videotape peer/other modeling to self-directed mental rehearsal (a covert modeling procedure) and a no-training (physical practice) control condition in training a mechanical device assembly task. Eighty male and female college students were introduced to the assembly task in a timed pretest trial and then videotaped performing the assembly task in a second trial. Over the next 4 days, subjects were randomly assigned to training conditions and repeatedly trained and tested in the mechanical device assembly task. The effects of training methods upon assembly times, self-efficacy expectations regarding assembly task performance, and subjective impressions of the nature and usefulness of training were examined. Superior assembly performance over initial training and at 4 months post-training follow-up was observed for the self-directed mental rehearsal training condition and discussed.